Selectives (“topic markers”) on subordinate clauses - Wälchli Bernhard (Linguistics)
This typological study based on data from a parallel text corpus is a two-step investigation of selectives (“topic markers”). First, a set of selectives in 81 languages from all continents is compiled on the basis of their occurrence with emphatic personal pronouns in contrast constructions. In a second step, it is explored how this set of markers is used across 19 subordinate clause domains. The results indicate that, despite much crosslinguistic diversity, the distribution of selectives across subordinate clauses is strongly constrained. Selectives in subordinate clauses are distributed following a tendency scale (no strict hierarchy, but no blatant exceptions): general relative clauses rank highest followed by conditional and temporal clauses with concessive and purpose clauses ranking lowest. No postposed subordinate clauses attract selectives. It is further found that selectives tend to occur at the end of the constituent which they have scope over where there is minimal risk of scope ambiguity. Despite the frequent occurrence of selectives on conditional clauses, selectives tend not to be conditional connectives unless this happens to be their grammaticalization source.